Padel, pickleball and wellbeing: a systematic review - Lauxtermann, Lena; Stubbs, Brendon (Frontiers in psychology, 2025)
Physical activity benefits mental health, yet the effects of emerging sports like padel and pickleball are understudied despite their accessibility and growth-300,000 amateur padel players worldwide and a 223.5% rise in U. S. pickleball players (2020-2023). This systematic review examines their association with mental health, wellbeing, and mental fatigue. An electronic search of Medline, PsycINFO, and Embase (inception to October 8, 2024; PROSPERO CRD42024594743) identified quantitative and observational studies on padel or pickleball participation and mental health or wellbeing outcomes. Fourteen of 71 studies ( 1,403) were included. Pickleball enhances wellbeing, life satisfaction ( < 0.05), happiness (r = 0.263, < 0.001), depression (r = -0.23, < 0.01), and social integration, especially in older adults. In padel, higher-level and match-winning players show increased self-confidence and reduced somatic anxiety; pre-competition anxiety rises, varies by gender and score, and is lower than in tennis. Mental fatigue increases with successive padel games, impairing accuracy ( = 0.05) and linking to elevated motivation. Mental health research on padel and pickleball has expanded, revealing distinct areas of focus. Padel studies primarily target performance aspects like self-confidence, anxiety, and mental fatigue, while pickleball research highlights wellbeing gains in life satisfaction, happiness, and social integration. However, gaps remain, particularly regarding the exploration of wellbeing in padel and performance-related mental health (e.g., anxiety, fatigue) in pickleball across diverse age groups to address these gaps. Future studies should address these gaps and consider diverse age groups to provide a more comprehensive understanding. PROSPERO: The Unique Identifier is CRD42024594743, and the publicly accessible URL is https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024594743.